Mineralogical signs of rare-metal and semi-precious ore mineralization in the Murzinskaya-Aduyskaya beryllium (gemstone) subprovince - Popov Mikhail Petrovich (Федеральное государственное бюджетное образовательное учреждение высшего образования «Уральский государственный горный университет», 2016)
The paper considers problems of establishing mineralogical signs of rare-metal and semi-precious ore mineralization in the territory of Murzinskaya-Aduyskaya beryllium (gemstone) subprovince, which is part of Murzinsko-Adamovsko-Mugodzharskaya rare-metal zone. Beryllium specialization of subprovince is caused by the extensive development of 260-300 mln years old collisional granites enriched with beryllium, tantalum, lithium, cesium, tungsten. Beryllium mineralization on the studied objects is timed to Apo ultramafic or Apo mafic glimmerites, which occur along the eastern contact of Murzinskiy (Glinskoye, Verhne-Susanskoe), Aduyskiy (deposits and occurrences of Ural emerald band) and Kamensky (Mines of Kuznetsov, Kamenskoye) Upper Paleozoic granite massifs. At the stage of general search, minerals-indicators of ore-bearing are most interesting. These issues are a part of search mineralogy researches, aimed at the development of mineralogical search criteria of the mineral deposits. As a result of the works author establishes mineralogical characteristics and patterns, which one can use for search of rare-metal and semi-precious ore mineralization: direct search mineralogical signs on the territory of Murzinskaya-Aduyskaya beryllium (gemstone) subprovince are findings of primary beryllium minerals (beryl, emerald, chrysoberyl, alexandrite, phenacite, euclase) and findings of mica veins and complexes, preferably ones that have phlogopite composition; indirect mineralogical signs are findings of secondary beryllium minerals (bavenite, bertrandite, Be-margarit, euclase); pink and purple fluorites, encountered in mica complexes within Murzinskaya-Aduyskaya gemstone subprovince, can be a direct mineralogy sign of semi-precious mineralization (emerald, chrysoberyl, alexandrite); positive europium anomalies in fluorite in the exploratory work are an indirect indication of the ore beryl mineralization; upon finding high positive anomalies of BeO, detected by gamma-neutron and photo-neutron methods at the operational exploration stage, one should check them using mineralogical methods (visual inspection, X-ray analysis) to determine the presence of secondary minerals of beryllium (bavenite, bertrandite) or minerals of fragile mica group, bityite-Be-margarit.
Keywords: УРАЛ; РЕДКОМЕТАЛЛЬНЫЕ МЕСТОРОЖДЕНИЯ; ИЗУМРУД; БЕРИЛЛ; АЛЕКСАНДРИТ; САМОЦВЕТЫ; URAL; RARE METAL DEPOSITS; EMERALD; BERYL; ALEXANDRITE; GEMSTONES; 549(470.5) + 550.81